2014
DOI: 10.12970/2310-9874.2014.02.03.2
|View full text |Cite
|
Sign up to set email alerts
|

What Everybody is Doing but No One is Talking About: Use of Complementary and Alternative Medicine in the ANCA Associated Vasculitis Population

Abstract: The use and impact of complementary and alternative medicine (CAM) for anti-neutrophil cytoplasmic antibody (ANCA) associated vasculitis (AAV) has not been reported. AAV patients seeking care at our center inquired about CAM, prompting a formal study. Study objectives were to discern how many AAV patients used CAM and its perceived helpfulness in disease management.Methods-AAV patients completed a CAM questionnaire between July 2011 and May 2012. Patients were 18 years or older and had biopsy proven and/or cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The I-CAM-Q was found to have low face validity and acceptability across five European Union (EU) countries: many terms, including types of practitioners, practices/therapies and product categories, were unknown to, or misunderstood by, participants as definitions were not provided in the tool [ 18 ]. Several countries adapted the I-CAM-Q by modifying the list of practitioners, practices/therapies and product categories [ 19 , 22 , 23 ], and question response options (e.g. perceived ‘helpfulness’ was changed to ‘benefit’ [ 24 ]) to suit their local context; in some countries, changes to the questionnaire were so substantial [ 17 , 25 ] that the original intention for a standardised tool may have been compromised.…”
Section: Introductionmentioning
confidence: 99%
“…The I-CAM-Q was found to have low face validity and acceptability across five European Union (EU) countries: many terms, including types of practitioners, practices/therapies and product categories, were unknown to, or misunderstood by, participants as definitions were not provided in the tool [ 18 ]. Several countries adapted the I-CAM-Q by modifying the list of practitioners, practices/therapies and product categories [ 19 , 22 , 23 ], and question response options (e.g. perceived ‘helpfulness’ was changed to ‘benefit’ [ 24 ]) to suit their local context; in some countries, changes to the questionnaire were so substantial [ 17 , 25 ] that the original intention for a standardised tool may have been compromised.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a well-known example is the use of cannabinoids in alleviating the symptoms of neurological diseases such as Parkinson's disease, as well as several other common complex disorders such as a multiple sclerosis and epilepsy [14][15][16][17]. In a study of patients with antineutrophil cytoplasmic antibody-associated vasculitis, a rare inflammatory disease, 81% of participants reported using at least one type of CIM to aid disease management with positive perceptions surrounding their efficacy, yet just 24% of participants discussed these CIM with their HCP [18]. A 2013 Cochrane systematic review of randomised control trials for creatine dietary supplements identified an improvement in rare hereditary muscular diseases [19].…”
Section: Introductionmentioning
confidence: 99%